Social communication and youth problems " Field research " Facebook, Twitter, Telcram, and Viber - Youssef stubbornness Zamel; Zeinab Mohamed Saleh (Zanco Journal of Humanity Sciences)
Social networking sites such as "Facebook, Twitter, Telcram, and Viber" occupied a larger part of the interests of many people, but rather a part of their daily lives, they communicate daily through virtual space with their friends anywhere near or on the edges of the earth, friendships that are not separated by political, national or systemic borders. Some of these friends devote more time to these friends than they do to their traditional friends outside the Internet, and these sites and the like have revolutionized human relations and contributed to the events of great social change. The negative trends that social media networks sometimes pose constitute psychological, educational and social problems, especially for their youth users.